Age and Sex Disparities in Discharge Statin Prescribing in the Stroke Belt: Evidence From the Reasons for Geographic and Racial Differences in Stroke Study. Issue 8 (2nd August 2017) - Albright, Karen C.; Howard, Virginia J.; Howard, George; Muntner, Paul; Bittner, Vera; Safford, Monika M.; Boehme, Amelia K.; Rhodes, J. David; Beasley, T. Mark; Judd, Suzanne E.; McClure, Leslie A.; Limdi, Nita; et al.
Abstract : Background: Stroke is a costly and debilitating disease that disproportionately affects blacks. Despite the efficacy of statins, evidence suggests racial disparities may exist in statin prescribing. Methods and Results: We analyzed discharge medications for participants hospitalized for an ischemic stroke during follow‐up of the REGARDS (Reasons for Geographic and Racial Differences in Stroke) study. Medications on admission and discharge were abstracted from medical records. Among the 666 eligible incident strokes (2003–2013), analyses were restricted to 323 participants who were not statin users at the time of admission and had no history of atrial fibrillation. Overall, 48.7% were prescribed a statin on discharge. In the Stroke Belt, participants aged 65 years and older were 47% less likely to be discharged on a statin compared with those younger than 65 years (relative risk [RR], 0.53; 95% CI, 0.38–0.74). This association was not observed in non–Stroke Belt residents. Outside the Stroke Belt, blacks were more likely than whites to be discharged on a statin (RR, 1.42; 95% CI, 1.04–1.94), while no black:white association was present among Stroke Belt residents (RR, 0.93; 95% CI, 0.69–1.26; P for interaction=0.228). Compared with women, men in the Stroke Belt were 31% less likely to be discharged on a statin (RR, 0.69; 95% CI, 0.50–0.94) while men outside the Stroke Belt were more likely to be discharged on a statin (RR, 1.38; 95% CI, 0.99–1.92; P for interaction=0.004). Conclusions: Statin discharge prescribing may differ among Stroke Belt and non–Stroke Belt residents, particularly in older Americans and men.